Trust and Role Based Access Control to Mitigate the Malicious Activities of Authenticated Users in Mobile Cloud Computing - Arif Mohammad Abdul, Sudarson Jena, Balraju M (International Journal of Advanced Science and Technology, 2020)
One of the emerging technologies of recent years is the mobile cloud computing, which aims to provide the vital need for richer applications and services of constrained resources. The major challenging issue of the mobile cloud computing is to provide the security with less overhead. In literature various authenticated key agreement mechanisms have been designed to address the security issues, as authenticated key agreement is the simple vital process to incorporate the security in computing technologies. However, there is a need to consider the authorization of the users, as the authenticated users may behave maliciously. Thus, the paper aim is to design the access control mechanism to mitigate the malicious activities causes by authenticated users by the computing the trust based on the user behavior. The results are showing that the proposed access control mechanism accurately detect and remove the malicious users.Keywords: Authentication, Access control, Trust, Role, Reputed users, Malicious users.